Exopolysaccharide-producing Streptococcus thermophilus strains as functional starter cultures in the production of fermented milks - De Vuyst, Luc (2003)
Relationships between exopolysaccharide (EPS) production (amount, molecular mass and sugar composition of the EPS) by different Streptococcus thermophilus strains as a functional starter culture, and textural characteristics (viscosity) of fermented milk and yoghurt have been studied. Five interesting heteropolysaccharide-producing strains have been tested, Both S. thermophilus LY03 and S. thermophilus CH101 produced the highest amounts of EPS and also displayed the highest apparent viscosities in fermented milk. S. thermophilus ST 111 and S. thermophilus STD differed considerably in EPS yields, but not in apparent viscosities of fermented milk. In addition, S. thermophilus ST 111 displayed a high variability in EPS amounts when cultivated in milk. In milk medium, S. thermophilus LY03 produced two heteropolysaccharides, a high-molecular-mass (HMM) EPS and a low-molecular-mass (LMM) EPS of the same composition (Gal/Glu/GalNAc = 3.4:1.4:1.0), S. thermophilus ST 111 produced only a HMM-EPS (Gal/Rha = 2.5:1.0), while S. thermophilus CH 101 (Gal/Glu = 1.0:1.0), S. thermophilus ST 113 (Gal/Glu/Rha/GalNAc = 1.7:3.9:1.5:1.0) and S. thermophilus STD (Gal/Glu/Rha/GalNAc = 3.5:6.2:1.2:1.0) produced only LMM-EPS. Both HMM-EPS and LMM-EPS solutions (S. thermophilus LY03) demonstrated a pseudoplastic character; HMM-EPS solutions of 0.2% (m/v) displayed a high consistency as well. Although its production of high EPS amounts, S. thermophilus LY03 resulted in relatively thin yoghurts, so that texture values did not directly correlate with EPS production capacity. Once structure/function relationships are known, one can determine the molecular properties of the isolated and purified EPS (molecular size, structural characteristics) from candidate strains to predict their potential in texture formation. For a final selection of interesting EPS-producing starter strains one should test the EPS production under yoghurt manufacturing conditions.